IDENTIFICATION OF EARLY DISORDERS OF GLOMERULAR FILTRATION RATE DEPENDING ON THE DEGREE OF OBESITY - Rakhmonova Nilufar Shodikulovna; Rakhmonova Mokhigul Shodikulovna; Tokhirjonova Aziza Tokhirjon qizi (Scholar Express Journals, 2022)
Obesity contributes to the increased risk of several diseases including cardiovascular diseases, chronic kidney diseases, diabetes, hypertension, metabolic syndrome. Obesity is well known as an independent risk factor for chronic kidney disease. Glomerular filtration rate (GFR) is the best routinely available estimate for kidney function and essential for detection and management of both acute kidney injury (AKI) and chronic kidney disease (CKD). Creatinine is the most frequently used biomarker for eGFR. Creatinine may vary with factors not related to kidney function such as gender, muscle mass, ethnicity, and dietary factors. Cystatin C is an alternative biomarker for GFR-estimation which does not depend on muscle mass and thus fairly constant with age and gender.
Keywords: Chronic kidney diseases; glomerular filtration rate; adiponectin; obesity